EXAMINING THE MISTAKES OF MOTHERS IN USING FEEDING BOTTLES - BEKAR, Pınar; ARIKAN, Duygu (Göbeklitepe Medical Science Journal, 2021)
Determine and examine the mistakes of mothers in using feeding bottles. This descriptive study was conducted at Atatürk University Research Hospital in the city center of Erzurum. The universe of the study consisted of all reachable mothers of 0-2 years old children hospitalized between April 2016-June 2017, and the sample consisted of 100 mothers who were in the hospital at the time of the application, who met the selection criteria and who agreed to participate in the study were included in the research. In the study, the data were collected by using a questionnaire that was developed by using the literature. Percentage and chi-square test analyses were performed in evaluating the data. In the study, it was determined that 68% of mothers fed their infants by using feeding bottle. 82,4% of the mothers using feeding bottle for their children caused bubbles in the bottle as they usually shook it up and down, and 86,8% gave the bottle in the half upright position. There was a significant difference between the state of children to use feeding bottle and educational background of mothers (p<0,05). Even though feeding bottle is not recommended for children from any age group, it is unfortunately used commonly in Turkey. According to this result, nurses are required to train mothers on avoiding the use of feeding bottles in order to increase breast milk and protect children from infections. On the other hand, helping mothers, who insist on using feeding bottle despite all efforts, for the proper use of bottle is important in terms of children’s health.